2020
DOI: 10.1021/acs.est.0c00192
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Geochemistry of Lead-210 and Polonium-210 Radionuclides in Public-Drinking-Water Supplies from Principal Aquifers of the United States

Abstract: On the basis of lifetime cancer risks, lead-210 (210Pb) and polonium-210 (210Po) ≥ 1.0 and 0.7 pCi/L (picocuries per liter), respectively, in drinking-water supplies may pose human-health concerns. 210Pb and 210Po were detected at concentrations greater than these thresholds at 3.7 and 1.5%, respectively, of filtered untreated groundwater samples from 1263 public-supply wells in 19 principal aquifers across the United States. Nationally, 72% of samples with radon-222 (222Rn) concentrations > 4000 pCi/L had 210… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 101 publications
1
34
0
Order By: Relevance
“…Potential sulfide concentrations for reducing samples were computed using measured aqueous iron concentration (assumed Fe +2 ) in equilibrium with pyrite or mackinawite. 109 Eh and pe are equivalent electrochemical descriptions of redox potential for a system in equilibrium. 110 However, waters at low temperature rarely achieve redox equilibrium, 111 so no single value of Eh or pe can be used to represent the redox state.…”
Section: ■ Methodsmentioning
confidence: 99%
“…Potential sulfide concentrations for reducing samples were computed using measured aqueous iron concentration (assumed Fe +2 ) in equilibrium with pyrite or mackinawite. 109 Eh and pe are equivalent electrochemical descriptions of redox potential for a system in equilibrium. 110 However, waters at low temperature rarely achieve redox equilibrium, 111 so no single value of Eh or pe can be used to represent the redox state.…”
Section: ■ Methodsmentioning
confidence: 99%
“…Geology is also important for the occurrence of various metals as well (Wright and Belitz 2010;Izbicki et al 2015;McClain et al 2019), except for the cosmogenic/fallout radionuclides (Gellis et al 2020). In public drinking water wells across the USA, lead-210 and polonium-210 radionuclides contaminate aquifers used for drinking water (Szabo et al 2020). The radionuclides Pb-210 and Po-210 do not co-occur in groundwater despite both being derived from Rn-222 due to control by decay rates and interactions with various aquifer materials such as the association of Pb-210 with felsic crystalline rocks, whereas Po-210 presence is dictated by reducing conditions and high pH (Szabo et al 2020).…”
Section: Identifying Risks Of Fss Based On Presence Of Radionuclides and Hydrogeologymentioning
confidence: 99%
“…Most recently, Szabo et al showed elevated levels of 210 Po (≥26 mBq L −1 ) in some drinking water supplies with groundwater source across the United States. 23 Thus, a rapid analytical technique of 210 Po in water would be beneficial for routine screening and health risk safeguard. At present, the most common method for 210 Po measurements is alpha spectrometry, 2 which involves the electrodeposition of 210 Po onto a silver disc in the standard protocol.…”
Section: Introductionmentioning
confidence: 99%